NK Cell and CD4+FoxP3+ Regulatory T Cell Based Therapies for Hematopoietic Stem Cell Engraftment - Antonio Pierini; Maite Alvarez; Robert S. Negrin (Hindawi Limited, 2016)
Allogeneic hematopoietic cell transplantation (HCT) is a powerful therapy to treat multiple hematological diseases. The intensive conditioning regimens used to allow for donor hematopoietic stem cell (HSC) engraftment are often associated with severe toxicity, delayed immune reconstitution, life-threatening infections, and thus higher relapse rates. Additionally, due to the high incidence of graft versus host disease (GvHD), HCT protocols have evolved to prevent such disease that has a detrimental impact on antitumor and antiviral responses. Here, we analyzed the role of host T and natural killer (NK) cells in the rejection of donor HSC engraftment as well as the impact of donor regulatory T cells (Treg) and NK cells on HSC engraftment. We review some of the current strategies that utilize NK or Treg to improve allogeneic HCT therapy in order to accomplish better HSC engraftment and immune reconstitution and achieve a lower incidence of cancer relapse, opportunistic infections, and GvHD.